Archetypes, madness and maternity in the Puppetry (Móin-Móin Magazine - Studies in the Art of Puppetry, 2020)
The article talks about the dramaturgical construction of the female characters of theshow O Quadro de Todos Juntos by the puppetry group Pigmalião Escultura que Mexe andproblematizes the representation of the maternal figure through correspondences with thewritings of Jung, Foucault and Beauvoir. The objective is to discover possibilities for questioningfemale stigmas through artistic representation and contribute to reveal the foundations thatsupport the patriarchal and sexist imagery. The work reflects also about the construction ofevocative images in the production of a theater spectacle and the idiosyncratic processes of theviewer reception.